This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Cant we do it with sum of n integers 50 to 100
a very good method !!
sum of arithmetic progressions has this formula
Sn=(a+l)n/2,
where n is the number of terms, a is the first term and l is the last term
According to the question, there are 51 terms, with the first term being 50 and the last term being 100
so Sn=51 x (50+100)/2 =51 x 75 =3825
That is what I was gonna type @Chan... Thanks
x = ( 1 0 0 + 9 9 + … + 1 ) − ( 4 9 + 4 8 + … + 1 ) = 5 0 5 0 − 1 2 2 5 = 3 8 2 5
Because 1 + 2 + 3 + … + n = 2 1 n ( n + 1 ) .
I feel the easiest way is the find the average and then multiply it by the number of digits. Here the average is easy to find, i.e. 75. Then we know that from 50 to 100 there are 51 digits and the answer to their total is 75 * 51 = 3825
By using this formula:
S n = 2 n ( U n + a )
to find n we can use:
if n = 1 then the number is 5 0
so, U 1 = 5 0 , U n = 5 0 − 1 = 4 9 ′
U n = 1 0 0 , 4 9 ′ = 1 0 0 , n = 1 0 0 − 4 9 = 5 1
Subtitude:
S 5 1 = 2 5 1 ( 1 0 0 + 5 0 )
S 5 1 = 2 5 1 ( 1 5 0 ) = 5 1 × 7 5 = 3 8 2 5
We can do this question by sum of arithmetic progression formula.. Sn=n/2(a+an)....where a=first term and an=last term and n=no. of term
If we take these series like this.. 50,51,52.........98,99,100 Then here, a=50,common difference(d)=1 an=100 And an=a+(n-1)d,therefore.. 100=50+(n-1)1 n=51 So, Now, Sn=51/2(50+100) Sn=3825(answer)
1+2+3+.......+100=(100×101)/2=5050 1+2+3+......+49=(49×50)/2=1225
. '. 50+51+52+.....100=5050-1225=3825
Equation=n×(n+1)/2
sum of n numbers = n(n+1)/2. so for first 49 numbers 49(49+1)/2 = 25 49. for first 100 numbers 100(100+1)/2 = 50 101 Then subtract 50(101)-25(49) = 3825
Using the formula k = a ∑ a + n k = 2 ( n + 1 ) ( 2 a + n ) as shown in this problem
So 2 ( 2 × 5 0 + ( 1 0 0 − 5 0 ) ) ( ( 1 0 0 − 5 0 ) + 1 ) = 2 1 5 0 × 5 1 = 3 8 2 5
d = − 1
a n = a 1 + ( n − 1 ) ( d )
5 0 = 1 0 0 + ( n − 1 ) ( − 1 )
n = 5 1
S = 2 n [ ( 2 a 1 + ( n − 1 ) ( d ) ] = 2 5 1 [ 2 ( 1 0 0 ) + ( 5 0 ) ( − 1 ) ] = 3 8 2 5
Subtract the sum of 1st 49 terms from
Sum of 1st 100 terms
5050-1225=3825
Since i = 1 ∑ n i = 2 1 n ( n + 1 )
Therefore the given sum will be 2 1 0 0 ( 1 0 0 + 1 ) − 2 4 9 ( 4 9 + 1 )
= 5 0 5 0 − 1 2 2 5
= 3 8 2 5
There are a number of ways to approach this problem.
Problem Loading...
Note Loading...
Set Loading...
We were given that x = 1 0 0 + 9 9 + 9 8 + ⋯ + 5 0
+ 1 0 0 5 0 1 5 0 + + + 9 9 5 1 1 5 0 + + + 9 8 5 2 1 5 0 + + + 9 7 5 3 1 5 0 + + + ⋯ ⋯ ⋯ + + + 5 0 1 0 0 1 5 0
So 2 x = 5 1 ( 1 5 0 ) ⟹ x = 2 5 1 ( 1 5 0 ) = 3 8 2 5